The solution to given system of equations is (x, y) = (2, -1)
Solution:
Given system of equations are:
-1x + 2y = -4 -------- eqn 1
4x + 3y = 5 ------- eqn 2
We can solve the above system of equations by elimination method
Multiply eqn 1 by 4
4(-1x + 2y = -4)
-4x + 8y = -16 ------ eqn 3
Add eqn 2 and eqn 3
4x + 3y = 5
-4x + 8y = -16
( + ) --------------------
0x + 11y = -16 + 5
11y = -11
y = -1
Substitute y = -1 in eqn 1
-1x + 2(-1) = -4
-x -2 = -4
-x = -4 + 2
-x = -2
x = 2
Check the answer:
Substitute x = 2 and y = -1 in eqn 2
4x + 3y = 5
4(2) + 3(-1) = 5
8 - 3 = 5
5 = 5
Thus the obtained answer is correct
Thus the solution to given system of equations is (x, y) = (2, -1)